Ireland : Selected Issues. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper presents a description of fiscal developments in Ireland since 1980. It attempts to decompose the improvement in the fiscal accounts into contributions from pure fiscal policy measures and contributions from other factors. Fiscal policy in 1997 and the budget for 1998 are outlined, and a discussion of the implications of the Stability and Growth Pact for policy formulation in Ireland is presented. The paper also examines the supervision system in Ireland and the performance of lending institutions.